"It Was Actually Pretty Easy": COVID‐19 Compliance Cost Reductions in the WIC Program. (9th September 2021) - Barnes, Carolyn; Petry, Sarah
Abstract: In recent years, scholars have examined the barriers to accessing public assistance benefits. Research identifies learning, compliance, and psychological costs as deterring program use. Compliance costs reflect the burdens of following program rules, which may entail providing documentation, responding to discretionary demands of bureaucrats, or attending appointments to maintain benefits. Studies identify one element of compliance costs—quarterly appointments—as a barrier to continued WIC participation. This article draws on 44 in‐depth qualitative interviews with participants in the Special Supplemental Nutrition Assistance Program for Women, Infants, and Children (WIC). We examine how WIC participants perceive the reduction of compliance costs following the implementation of remote appointments in response to the COVID‐19 pandemic. WIC participants report satisfaction with remote appointments and a reduction in the compliance costs of accessing and maintaining benefits. We conclude by recommending longer term changes to policy and practices to increase access and continuity in WIC receipt.